Pertumbuhan dan Hasil Bawang Merah (Allium Ascalonicum L.) dengan Pemakaian Beberapa Jenis Mulsa dan Dosis Pupuk Kandang Ayam - Yanny Savitri; Indra Dwipa; Warnita Warnita (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
Shallot (Allium ascolanicum L.) is one of the horticultural crops that is widely consumed by humans. This study aims to obtain interaction the type of mulch and doses of chicken manure on the growth and yield of shallots. This Research was conducted at Panai Pasir Talang , Muara Labuh, South Solok Regency with a height of ± 430 meters above sea level, in December 2018 to February 2019. The research method is an experiments used factorial complete randomized design with two factors. Factors I is the type of mulch (black plastic mulch, silver plastic mulch, rice straw mulch) and factors II is chicken manure (10 tons / ha, 20 tons / ha and 30 tons / ha).. The results showed that there was no interaction between the use of several types of mulch with chicken manure doses on the growth and yield of shallots. The use of black plastic mulch yielded the best results on fresh tuber weight per plot and per hectare of onion namely 1,643 kg / plot and 11.74 tons / ha. The dose of chicken manure of 20 tons / ha gave the best influence on plant height, number of leaves, fresh tuber weight per clump, per plot and per hectare as well as wind dry weight per clump, per plot and per hectare of onion.